Biobased pH-responsive and self-healing hydrogels prepared from O-carboxymethyl chitosan and a 3-dimensional dynamer as cartilage engineering scaffold. (15th September 2020) - Yu, Rui; Zhang, Yan; Barboiu, Mihail; Maumus, Marie; Noël, Danièle; Jorgensen, Christian; Li, Suming
Highlights: Dynamic hydrogels are prepared from carboxymethyl chitosan and 3-D dynamer by imine bond formation. The resulting hydrogels exhibit excellent pH-sensitive swelling properties. The hydrogels present outstanding self-healing properties. The hydrogels exhibit good cytocompatibility. The hydrogels present great potential for applications in tissue engineering. Abstract: Novel dynamic hydrogels were prepared from O-carboxymethyl chitosan (CMCS) and a water soluble dynamer Dy via crosslinking by imine bond formation using an environmentally friendly method. Dy was synthesized by reaction of Benzene-1, 3, 5-tricarbaldehyde with Jeffamine. The resulting soft hydrogels exhibit a porous and interconnected morphology, storage modulus up to 1400 Pa, and excellent pH-sensitive swelling properties. The swelling ratio is relatively low at acidic pH due to electrostatic attraction, and becomes exceptionally high up to 7000 % at pH 8 due to electrostatic repulsion. Moreover, hydrogels present outstanding self-healing properties as evidenced by closure of split pieces and rheological measurements. This study opens up a new horizon in the preparation of dynamic hydrogels with great potential for applications in drug delivery, wound dressing, and in particular in tissue engineering as the hydrogels present excellent cytocompatibility.